Pendampingan dalam Pembuatan Rencana Anggaran Biaya (RAB) untuk Proyek Sederhana di Desa Lubangbuaya, Kecamatan Setu, Kabupaten Bekasi - Bintang Bagas; Muhammad Ilyas Sikki; Setyo Supratno; Rika Sylviana (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Assistance in preparing the Budget Plan (RAB) through the Community Service Program (KKN) aims to help the Lubangbuaya Village community understand and apply budget management concepts for the construction of a two-story house. This activity consists of several stages, including socialization, training, and direct simulation, to provide comprehensive knowledge on systematic and transparent RAB preparation techniques. The results indicate that the community is better equipped to prepare RAB, understand the key components of budget calculation, and recognize the importance of RAB in ensuring project efficiency and accountability. It is expected that the acquired skills can be applied to various village development projects, leading to more effective and structured financial management.supports more sustainable village development.